Unravelling mechanisms of protein and lipid oxidation in mayonnaise at multiple length scales. (15th February 2023) - Yang, Suyeon; Takeuchi, Machi; Friedrich, Heiner; van Duynhoven, John P.M.; Hohlbein, Johannes
Highlights: LDL particles engage in multi-scale aggregation in the continuous phase of mayonnaise. Micronscale localisation of protein free radicals with a fluorescent spintrap. Local protein oxidation induced by local lipid oxidation At the droplet interface dispersed proteins undergo lipid-radical induced oxidation. Protein oxidation also occurs in LDL particles in the continuous phase. Abstract: In mayonnaise, lipid and protein oxidation are closely related and the interplay between them is critical for understanding the chemical shelf-life stability of mayonnaise. This is in particular the case for comprehending the role of low-density lipoprotein (LDL) particles acting as a main emulsifier. Here, we monitored oxidation and the concomitant aggregation of LDLs by bright-field light microscopy and cryogenic transmission electron microscopy. We further probed the formation of protein radicals and protein oxidation by imaging the accumulation of a water-soluble fluorescent spin trap and protein autofluorescence. The effect of variation of pH and addition of EDTA on the accumulation of the spin trap validated that protein radicals were induced by lipid radicals. Our data suggests two main pathways of oxidative protein radical formation in LDL particles: (1) at the droplet interface, induced by lipid free radicals formed in oil droplets, and (2) in the continuous phase induced by an independent LDL-specific mechanism.